2006
DOI: 10.5194/aab-49-593-2006
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the development of serum biochemical parameters in two laying hen strains – a comparative study

Abstract: A follow-up, comparative study was designed for the description of differences between two divergent laying hen strains, a Leghorn type and a medium heavy body (MHB) genotype (Hy-Line Brown), in chemical body composition and serum biochemical parameters determined at 3, 4, 6, 8, 10, 12, 14, 18, 20, 25, 30, 52 and 72 weeks of age; each time 5 birds of both genotypes were analysed and exterminated for body composition analysis.Resulting from the genotype-associated differences, the bodyweight of the populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 23 publications
7
18
0
Order By: Relevance
“…On the other hand, Koelkebeck and Odom (1995) reported no significant changes in plasma potassium levels under ambient temperature. Mean values similar to those received in this study were reported by Suchy et al (1989;, Gezen et al (2005), and Gyenis et al (2006). Lower mean plasma potassium levels were reported by Koelkebeck and Odom (1995).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…On the other hand, Koelkebeck and Odom (1995) reported no significant changes in plasma potassium levels under ambient temperature. Mean values similar to those received in this study were reported by Suchy et al (1989;, Gezen et al (2005), and Gyenis et al (2006). Lower mean plasma potassium levels were reported by Koelkebeck and Odom (1995).…”
Section: Discussionsupporting
confidence: 78%
“…A considerable increase in plasma Ca levels at the beginning of laying period and subsequent gradual increase was also observed by Cerolini et al (1990), Gyenis et al (2006), Filizciler et al (2002), and Strakova et al (1994). On the contrary, Burnham et al (2003) described an increase in calcium levels before the laying period and a decrease in calcium levels during the laying.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Increase of TAG concentration in subsequent samplings attracts an attention, because laying rate and deposition in egg yolks is subject to a decrease. Similar tendencies were noted by Gyenis et al (2006) in the study on Hy-Line Brown line hens. In turn, in Hy-line laying hens between 28 th and 30 th wk of life, the values in the range of 10.87-12.08 mmol/l were observed (Kralik et al 2006).…”
Section: Discussionsupporting
confidence: 71%
“…Similarly, Gunaratne and Boorman (1996) could measure no significant trends in plasma Ca during the day. The serum Ca content was the same at both ages which is in contrast with Brackpool et al (1996), Suchy et al (2004), Gyenis et al (2006), and Pavlik et al (2009) who demonstrated a gradual decrease in plasma Ca with age. However, differences in serum Ca between laying hens and broiler breeders were the same as reported by Suchy et al (2004) who described highly significantly lower plasma Ca levels in broiler breeders than in egg type hens.…”
Section: Discussionmentioning
confidence: 41%